Calculation of Stability Radii for Combinatorial Optimization Problems - Nilotpal Chakravarti; Albert P.M. Wagelmans (Tinbergen Institute, 1997)
We present algorithms to calculate the stability radius of optimal or approximate solutions of binary programming problems with a min-sum or min-max objective function. Our algorithms run in polynomial time if the optimization problem itself is polynomially solvable. We also extend our results tothe tolerance approach to sensitivity analysis.
Keywords: 330; stability radius; sensitivity analysis; postoptimal analysis; tolerance approach; binary programming; computational complexity; Mathematische Optimierung; Theorie